2017
DOI: 10.1089/neu.2016.4583
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Day Recordings of Wearable Sensors Are Valid and Sensitive Measures of Function and Independence in Human Spinal Cord Injury

Abstract: Wearable sensor assessment tools have proven to be reliable in measuring function in normal and impaired movement disorders during well-defined assessment protocols. While such assessments can provide valid and sensitive measures of upper limb activity in spinal cord injury (SCI), no assessment tool has yet been introduced into unsupervised daily recordings to complement clinical assessments during rehabilitation. The objective of this study was to measure the overall amount of upper-limb activity in subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…We arbitrarily chose a Z -score of 2 as 95.4% of the values fall within 2 SDs from the mean of paraplegic subjects. This is because we have previously shown that paraplegic subjects do not show any limb-use laterality (22) and their limb-use laterality indexes are similar to healthy subjects (43). In analyzing only the lateralized-group, we showed that lateralized cervical subjects significantly decreased limb-use laterality but remained impaired with limb-use laterality values in the same range as a group of chronic tetraplegic subjects who we measured previously (31).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…We arbitrarily chose a Z -score of 2 as 95.4% of the values fall within 2 SDs from the mean of paraplegic subjects. This is because we have previously shown that paraplegic subjects do not show any limb-use laterality (22) and their limb-use laterality indexes are similar to healthy subjects (43). In analyzing only the lateralized-group, we showed that lateralized cervical subjects significantly decreased limb-use laterality but remained impaired with limb-use laterality values in the same range as a group of chronic tetraplegic subjects who we measured previously (31).…”
Section: Discussionmentioning
confidence: 91%
“…Previously, we have shown that proximal muscle function was strongly related to overall AC during acute inpatient rehabilitation (22). In the present study, we extend these findings and show that this relationship becomes weaker over time.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations